The Influence of Transportation Costs on the Prices of Basic Food Goods in Timika City - Robaha, Aprilia Melssa; Parrangan, Immanuel Kadang; Kramandondo, Margaretha; Arapi, Rahmat (ProBisnis : Jurnal Manajemen, 2024)
The city of Timika, located in Papua, Indonesia, has high transportation costs due to limited access and inadequate infrastructure. This has an impact on the prices of basic food items in the city, which are generally higher compared to other regions in Indonesia. This research aims to analyze the influence of transportation costs on the prices of basic food items in Timika City. This research aims to analyze the influence of transportation costs on the prices of basic food items in Timika City over the last 4 years (2020-2023). This research uses quantitative methods with a descriptive approach and simple linear regression. Data was collected through secondary techniques and literature studies. Data analysis was carried out using simple linear regression techniques. The research results show that there is a positive and significant relationship between transportation costs and the prices of basic food items in Timika City. This means that the higher the transportation costs, the higher the prices of goods and services in Timika City. This research also found several factors that influence transportation costs in Timika City, including long distances, inadequate transportation infrastructure, high fuel costs, and high port and airport costs. Based on the research results, it was concluded that transportation costs have a significant influence on the prices of basic food items in Timika City. The government needs to make various efforts to reduce transportation costs and prices of goods and services in Timika City, such as building adequate transportation infrastructure, increasing the operational efficiency of ports and airports, providing subsidies to entrepreneurs, and increasing the production of goods and services in Timika City.